All chemical vapor deposition growth of MoS2:h-BN vertical van der Waals heterostructures. - Wang, S; Wang, X; Warner, J (American Chemical Society, 2015)
Vertical van der Waals heterostructures are formed when different 2D crystals are stacked on top of each other. Improved optical properties arise in semiconducting transition metal dichalcogenide (TMD) 2D materials, such as MoS2, when they are stacked onto the insulating 2D hexagonal boron nitride (h-BN). Most work to date has required mechanical exfoliation of at least one of the TMDs or h-BN materials to form these semiconductor:insulator structures. Here, we report a direct all-CVD process for the fabrication of high-quality monolayer MoS2:h-BN vertical heterostructured films with isolated MoS2 domains distributed across 1 cm. This is enabled by the use of few-layer h-BN films that are more robust against decomposition than monolayer h-BN during the MoS2 growth process. The MoS2 domains exhibit different growth dynamics on the h-BN surfaces compared to bare SiO2, confirming that there is strong interaction between the MoS2 and underlying h-BN. Raman and photoluminescence spectroscopies of CVD-grown MoS2 are compared to transferred MoS2 on both types of substrates, and our results show directly grown MoS2 on h-BN films have smaller lattice strain, lower doping level, cleaner and sharper interfaces, and high-quality interlayer contact.